Nursing Challenges in End-of-Shift Clinical Handover - Watin Ayad Bashir Alanazi; Tahani Mohammed Ail Alshamari; Nada Turki Munawir Alruwaili; Areej Ghassen Naha Alenazi; Alshammari, Wadha Mohammed; Mohammed Ali Mohammed Althagafi; Ahmed Turef Alrawaili; Majed Azzab Mutraf Alanazi; Mohamed Mudhhi Al Ruwwaili; Manal Kalied Sabr Alrawaili; Norah Nazal D Alshammari (International Journal of Computational and Experimental Science and Engineering, 2024)
End-of-shift clinical handover is a critical process in nursing that ensures continuity of care and patient safety. However, it presents several challenges that can impact the effectiveness of information transfer. One prominent challenge is time constraints; nurses often have limited time to complete handovers amidst their other responsibilities. This hurried exchange can lead to incomplete or inaccurate information transfer, increasing the risk of errors in patient care. Additionally, variations in handover practices between shifts and among different teams can further complicate the process, resulting in missed critical updates regarding patient conditions or interventions that need to be carried out. Effective communication plays a crucial role in mitigating these challenges, yet it can be hampered by various factors such as high workload, high-stress environments, and interruptions during handover. Inconsistent documentation practices can also contribute to misunderstandings among nursing staff. To improve end-of-shift clinical handover, healthcare institutions are increasingly adopting standardized protocols and utilizing technology, such as electronic health records and handheld devices, to streamline information sharing. Furthermore, fostering a culture of collaboration and open communication among healthcare teams can enhance the quality of handovers, ultimately ensuring that patient care is seamless and safe.